Navigating the intersections of gender equity and quality education in India’s SDG commitments - Sheoran, Sonika (American Journal of STEM Education, 2026)
Qualitative research analyzes the operational connection between Rajasthan and Haryana's gender-responsive educational programs and their support for SDG 4 and SDG 5. The research employs feminist critical policy analysis and comparative case studies to analyze state-level initiatives through an examination of the Rajiv Gandhi Scheme for Empowerment of Adolescent Girls in Rajasthan and Beti Bachao Beti Padhao actions in Haryana concerning intersectional equity application. The analyzed data shows development requires gender equity, but both states deploy their policies towards short-term results rather than transformative changes.  The research uses marginalized voices to create advanced gender equity perspectives in education that move past standard metrics and provide systematic solutions for India to achieve sustainable development goals.